INVESTIGATION OF SURVIVAL RATIO AND GROWTH RATE IN OFFSPRING OF SALMO TRUTTA CASPIUS - H. Asaeian; M. Mosavi; M. Haghighi; M. Rezvani (‬‭Majallah-i ̒Ilmī-i Shīlāt-i Īrān, 2007)
We investigated the survival ratio and the growth rate of offspring of Salmo trutta caspius produced from three groups of brood fish in Shahid Bahonar Rearing and Breeding Center in Klardashtin 2005. The three groups of brood fish belonged the early, mid, and late-migration period. The sampling was done randomly, and in each group 15 female and 5 male fish were included. After spawning and hatching, 22500 eggs were used in each group (3 treatments, repeated 9 times). The results showed no significant difference in the survival ratio of the egg and larva in the three groups of the brood fish in each stage of evolution up to two months after the start of active feeding (P>0.05). However, after the start of active feeding there was a significant difference (P<0.05) in the growth ratio of offspring produced in the groups aged one and two months. The growth ratio of the same age offspring in the first group was higher than those in the third group (P<0.05); but there was no significant difference between the first and the second group, or between the second and the third group (P> 0.05). Based on the results, we suggest that the brood fish from the early migration period are more suitable for producing offspring and their offspring pass through the smoltification stage more rapidly. However, in terms of genetic diversity, it would be appropriate to use brood fish from all migration periods.